GAMELAN SELAP - PADA WAYANG GOLEK SUNDA - Sopandi, Caca (LP2M ISBI Bandung, 2015)
The show of wayang golek purwa in Sunda has under gone considerable creativities by using gamelan selap as the karawitan element. The use of gamelan selap by the puppeteers in the show of waang golek purwa becomes so phenomena that its background needs to be known. Gamelan selap is created as the fulfillment of laras/surupan which has not been fulfilled so that there is an innovation in the instruments which produce several series of tones as the new formation. Gamelan selap is also used as the puppeteer 's attraction to get market opportu nities. This is proven by the increase ownership of gamelan selap by the groups of wayang golek purwa in West Java. Nevertheless, the use of gamelan selap has weakness on percussion technique problems, especially on the bar instrument. At Gamelan selap the tones can be automatically stepping passes through three or even four tones. The organological improvements are therefore required in order the use gamelan selap really brings significant changes, not only for the benefit of working on the composition but also for the sake of aesthetics.